THE CRITICAL EVALUATION OF GREEN MARKETING IN MIDDLE EAST - shukri, Sakinah mohd; Yajid, Mohd Shukri Ab; Ferdous (International Journal of Psychosocial Rehabilitation, 2020)
With the above context in mind and the possibilities and challenges it all represents, we began our search for a (green) company with a green product to market. We found this an intriguing project. Firstly, because of Laie Asls limited size and resources, representing some interesting challenges. Secondly, because of the market being a market of distribution and business to business dealing with both the potential business customers, but also having an end user to consider. Thirdly, because of the complexity of the roles of the parties involved seeing that Laie Asl has a contract to be the Iranian distributor for another manufacturer, wholesale distributor and brand, representing the question of Laie Asls own visibility, image and decision‐making rights in the marketing and sales process. And last, but not least, because it is interesting to see how this manufacturing and sales structure corresponds with the market demands for green authenticity as described above.